KOLABORASI SOSIAL MEMBANGUN MASYARAKAT UNTUK MEMPERTAHANKAN KOMODITI UNGGULAN KARET ALAM DI KAB.KUATAN SINGINGI RIAU - Sunanto Sunanto; Sunaryo Sunaryo; Israyadi Israyadi; Bahrudin Bahrudin; Ida Zahrina; Indra Yasri (Jurnal Abdimas Bina Bangsa, 2024)
The Berkah Basamo Rubber Farmers Group Association (Gapoktan) in Lubuk Terantang Village already has two rubber downstream product development workshops. The Kuantan Singingi Rubber Farmers Association (APKARKUSI) has facilitated the two buildings with several equipment to support downstream rubber production, including hot press machines, molding, compressors, creeper machines, tire retreading machines, and buffing machines. Apart from that, APKARKUSI has also facilitated several people from the Lubuk Terantang Village Youth Organization to be given training in making downstream rubber products at the Industrial Research and Standardization Center (Baristand), Palembang. The problem currently faced by target partners is that the production equipment is less functional, so farmers cannot produce downstream rubber with higher economic value. Apart from that, target partners also still need more intensive assistance and training, both in the production process and marketing their products. The solutions offered in this kosabangsa program are improving the institutional structure of target partners, improving businesses initiated by partners, improving partner income and welfare